2008
DOI: 10.1158/1078-0432.ccr-07-4995
|View full text |Cite
|
Sign up to set email alerts
|

Regional Hypoxia in Glioblastoma Multiforme Quantified with [18F]Fluoromisonidazole Positron Emission Tomography before Radiotherapy: Correlation with Time to Progression and Survival

Abstract: Purpose: Hypoxia is associated with resistance to radiotherapy and chemotherapy and activates transcription factors that support cell survival and migration.We measured the volume of hypoxic tumor and the maximum level of hypoxia in glioblastoma multiforme before radiotherapy with [ Conclusions:The volume and intensity of hypoxia in glioblastoma multiforme before radiotherapy are strongly associated with poorer TTP and survival. This type of imaging could be integrated into new treatment strategies to target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
208
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(216 citation statements)
references
References 44 publications
7
208
0
1
Order By: Relevance
“…In such conditions, glucose is metabolized without consuming oxygen to produce lactate (anaerobic glycolysis) whereas oxygen is essential to fully metabolize glucose (oxidative phosphorylation) [10]. Hypoxia imaging has been reported to provide prognostic information in glioblastoma patients; for example, previous studies found that glioblastoma patients with a larger hypoxia volume (HV) in the tumor had shorter survival [11][12][13][14]. However, hypoxia imaging may reflect not only active tumor cells but also dying cells that could not survive severe hypoxic conditions [8].…”
Section: It Is Defined As Grade IV According To the 2007 World Healthmentioning
confidence: 99%
“…In such conditions, glucose is metabolized without consuming oxygen to produce lactate (anaerobic glycolysis) whereas oxygen is essential to fully metabolize glucose (oxidative phosphorylation) [10]. Hypoxia imaging has been reported to provide prognostic information in glioblastoma patients; for example, previous studies found that glioblastoma patients with a larger hypoxia volume (HV) in the tumor had shorter survival [11][12][13][14]. However, hypoxia imaging may reflect not only active tumor cells but also dying cells that could not survive severe hypoxic conditions [8].…”
Section: It Is Defined As Grade IV According To the 2007 World Healthmentioning
confidence: 99%
“…Our results in the first study are consistent with this previous data, except for the grade III patients, as all of our grade III gliomas were FMISO negative. Cher et al used 2 h as the waiting time before conducting the FMISO PET scanning, while the study here used 4 h. Many FMISO PET protocols have used 2 h as the uptake time [24,25,[27][28][29][30][31][32], while Thorwarth et al questioned the adequacy of 2 h for imaging of FMISO [34]. There, the kinetic analysis of dynamic datasets of FMISO PET suggested that the hot spots at 2 h did not reflect actual hypoxia but rather showed a high initial influx of the FMISO due to increased blood flow to the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the hypoxic volume is distinguished with tissue-to-blood ratios ! 1.2 in images acquired 2 h after FMISO injection with venous blood samples [28][29][30][31]. In brain tumor segmentation for MET PET, a tumor-to-normal ratio !…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations